Single-Cell Microwell Platform Reveals Circulating Neural Cells as a Clinical Indicator for Patients with Blood-Brain Barrier Breakdown - Zhang, Yu; Warden, Antony R.; Ahmad, Khan Zara; Liu, Yanlei; He, Xijun; Zheng, Minqiao; Huo, Xinlong; Zhi, Xiao; Ke, Yuqing; Li, Hongxia; Yan, Sijia; Su, Wenqiong; et al. (Research, 2021)
Central nervous system diseases commonly occur with the destruction of the blood-brain barrier. As a primary cause of morbidity and mortality, stroke remains unpredictable and lacks cellular biomarkers that accurately quantify its occurrence and development. Here, we identify NeuN + /CD45 − /DAPI + phenotype nonblood cells in the peripheral blood of mice subjected to middle cerebral artery occlusion (MCAO) and stroke patients. Since NeuN is a specific marker of neural cells, we term these newly identified cells as circulating neural cells (CNCs). We find that the enumeration of CNCs in the blood is significantly associated with the severity of brain damage in MCAO mice ( p < 0.05 ). Meanwhile, the number of CNCs is significantly higher in stroke patients than in negative subjects ( p < 0.0001 ). These findings suggest that the amount of CNCs in circulation may serve as a clinical indicator for the real-time prognosis and progression monitor of the occurrence and development of ischemic stroke and other nervous system disease.